38.1k views
1 vote
3(x - 2) + 4(2x - 6) = 6(x - 4) + 8(2x + 1) in need help plz ​

User Vardhan
by
4.5k points

1 Answer

6 votes

Answer:

x = -14/11

Explanation:

3(x - 2) + 4(2x - 6) = 6(x - 4) + 8(2x + 1)

Distribute each number to the left of each set of parentheses.

3x - 6 + 8x - 24 = 6x - 24 + 16x + 8

Add 24 to both sides.

3x - 6 + 8x = 6x + 16x + 8

Combine like terms on each side.

11x - 6 = 22x + 8

Subtract 22x from both sides:

-11x - 6 = 8

Add 6 to both sides:

-11x = 14

Divide both sides by -22:

x = -14/11

User Estarius
by
5.3k points